2021
DOI: 10.1111/nph.17288
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic, phylogenetic and functional diversity of root‐associated fungi in bromeliads: effects of host identity, life forms and nutritional modes

Abstract: Bromeliads represent a major component of neotropical forests and encompass a considerable diversity of life forms and nutritional modes. Bromeliads explore highly stressful habitats and root-associated fungi may play a crucial role in this, but the driving factors and variations in root-associated fungi remain largely unknown.We explored root-associated fungal communities in 17 bromeliad species and their variations linked to host identity, life forms and nutritional modes by using ITS1 gene-based highthrough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…Fungal communities were studied from MiSeq sequence libraries. Sequences were processed using the custom‐made python pipeline EGRETTA 1.3 (Leroy et al, 2021; Pierart et al, 2018). Contigs of paired‐end reads were assembled, cured by removing structural errors that lead to incomplete (offsets and short constructs) and mixed reads (chimeras and cross‐talks), and dereplicated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal communities were studied from MiSeq sequence libraries. Sequences were processed using the custom‐made python pipeline EGRETTA 1.3 (Leroy et al, 2021; Pierart et al, 2018). Contigs of paired‐end reads were assembled, cured by removing structural errors that lead to incomplete (offsets and short constructs) and mixed reads (chimeras and cross‐talks), and dereplicated.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies revealed, from microscopic observations, the presence of AMF and/or DSE in the roots of terrestrial and epiphytic bromeliads (Allen et al, 1993; Grippa et al, 2007; Lesica & Antibus, 1990; Lugo et al, 2009; Rabatin et al, 1993; Rowe & Pringle, 2005). Recently, Leroy et al (2021) used ITS1 region‐based high‐throughput sequencing (i.e., metabarcoding) and found a high diversity of root‐associated fungi in 17 bromeliad species having contrasting life forms and nutritional modes: mycorrhizal fungi such as AMF, ectomycorrhizal fungi (EcMF), orchid mycorrhizal fungi (OMF), and ericoid mycorrhizal fungi (ErMF) and non‐mycorrhizal fungi such as fungal endophytes (FE) including DSE. The community composition of endophytic fungi (including DSE) found in the root of A .…”
Section: Introductionmentioning
confidence: 99%
“…To preliminary validate our method of functional content profiling we used the t-SNE decomposition for gene content vectors. We expected that observed clusters would be associated with fungal taxonomy, which is according to literature data (Leroy et al, 2021;Wisecaver et al, 2014). To estimate the convergence of observed clusters and fungal taxonomy, the Rand Index (RI) was used.…”
Section: Data Collectionmentioning
confidence: 95%
“…Furthermore, bromeliad roots are associated to mycorrhizal and dark septate endophytes (DSE) fungi (Allen et al 1993, Rabatin et al 1993, Rowe and Pringle 2005, Grippa et al 2007, Lugo et al 2009). Recently, Leroy et al (2021) found bromeliad roots to have diverse fungal assemblages with 1) mycorrhizal fungi such as AMF, ectomycorrhizal fungi (EcMF), orchid mycorrhizal fungi (OMF) and ericoid mycorrhizal fungi (ErMF), and 2) non‐mycorrhizal fungi such as fungal endophytes (FE) including DSE. Fungal endophytes in bromeliad roots benefit plant nutrition and growth (Leroy et al 2019a).…”
Section: Introductionmentioning
confidence: 99%